Robust dead-beat synchronization of discrete chaotic systems and application to secure communications - LI Yu-xian (Tongxin xuebao)
A robust dead-beat synchronization method was presented for discrete chaotic systems using adaptive channel blind equalization and dead-beat chaotic synchronization. This method utilizes chaotic synchronization error as the en- ergy function and evolutionary programming to train the RNN, whose output was used as the driving signal for the cha- otic receiver. Furthermore, based on the robust dead-beat synchronization method, a new secure communication method was proposed.